All-Lignin-Based Thermoset Foams via Azide-Alkyne Cycloaddition and Their Fire Resistance after Oxidation - Jang Minjeong; Shin Hun Yi; Dawon Jang; Jo, Seong Mu; Kim, Sejung; Kim, Sung-Soo (AMER CHEMICAL SOC, 2022)
Lignin was utilized as a biosourced component of thermosetting polymers to demonstrate the valorization of the biorenewable feedstock. Multifunctional lignin macromonomers with azide groups and terminal alkyne moieties were synthesized, and their blend was transformed into thin films by direct hot pressing. Those films were continuously processed with thermal treatment at 150 degrees C to induce the azide-alkyne cycloaddition reaction without Cu-based catalysts, resulting in the formation of all-lignin-based thermoset foams. The resulting macroporous film was fully cross-linked with a higher gel fraction (>96%) and contained randomly distributed pores inside it due to the generation of gaseous products during the cross-linking process. Additional thermal treatment of all-lignin thermosets in air effectively oxidized the film to convert alkylene bridged to polyaromatic structures with abundant oxygen-containing functional groups, which substantially enhanced their flame resistance (UL 94 V-0 rated) with the increase in the limiting oxygen index value (23.4 -> 28.8%).